Bahasa Inggris - Ramadiva Muhammad Akhyar; Afita Nur Hayati; Sitti Syahar Inayah; Ida Suryani Wijaya (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2024)
Investigating women’s participation in politics might be beneficial for the improvements of communication studies, especially in political communication studies. This research’s objective is to analyze the involvement of a group of women in a religious Islamic movement in East Kalimantan, Indonesia. This research applied a descriptive qualitative research design by conducting semi- structured interviews to ten women from two political women groups in East Kalimantan. The results of the research suggest that the informants posit their acceptance to a particular male and female legislative candidates due to these candidates’ stances in religious beliefs and the candidates’ credibilities. The results suggest that these informants have a strong awareness to actively participate in politics, suggesting that women are aware of the importance of politics in their daily life.